Bangka Belitung economic growth analysis with solow theory - Devi Valeriani; M. Faisal Akbar; Ayu Wulandari; Rusdi Rusdi; Mardani Mardani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This research discusses the effect of installed power, Gross Fixed Capital Formation (GFCF), the number of workers on the Gross Domestic Product (GDP) of the Province of the Bangka Belitung Islands. The approach used by the researcher is descriptive quantitative. The data analysis technique used in this study is multiple linear regression using secondary data sourced from the Central Statistics Agency, namely panel data for the 2010-2019 period in the Province of the Bangka Belitung Islands. The results showed that the best model in panel data regression analysis of the factors that influence the GRDP of the Bangka Belitung Islands Province in this study was the Random Effect Model. Capital Per Worker, Life Expectancy, Average Length of Schooling, and Expected Length of Schooling are able to explain the GDP of 56.69 percent. Capital Per Worker, Life Expectancy, Average Length of Schooling, and Expected Length of School together have a significant effect on GDP. Partially, capital per worker has an insignificant negative effect on GDP, while life expectancy and average length of schooling have a significant positive effect on GDP. Expectations for the school year have a positive but not significant effect on GDP.